Corrigendum to "On Fixed Point Results for a Class of Generalized Mean Nonexpansive Mappings" - Ram, M. (Methods of Functional Analysis and Topology, 2021)
In this corrigendum, we offer a correction to the paper On fixed point results for a class of generalized mean nonexpansive mappings, Methods Funct. Anal. Topology, 26 (2020), no. 4, 356-372.